System of activities using flashcards as a didactic resource to improve vocabulary acquisition - Viñamagua Espinoza, Génesis Arleth; Loyola Pillajo Elsa Lucia (Machala: Universidad Técnica de Machala, 2024)
This thesis focuses on improving vocabulary acquisition through the implementation of system of activities using flash cards as a didactic resource. Following a positivist quantitative perspective, under an experimental design, it approaches the deficiencies identified in the lexical of 30 second baccalaureate parallel A students from Colegio de Bachillerato “Carmen Mora de Encalada. The use of theoretical methods was considered to support the object of study, and empirical methods were also used as evaluation instruments to obtain detailed results on the academic level of the students, confirming that the use of flash cards as a didactic resource contributes positively to lexical development and English language learning. se of flash cards as a didactic resource contributes positively to lexical development and English learning. This positive impact is attributed to the memorization and repetition strategy facilitated by a system of interactive and creative activities integrated into educational setting.
Esta tesis se centra en mejorar la adquisición de vocabulario mediante la implementación de un sistema de actividades utilizando flash cards como recurso didáctico. Siguiendo una perspectiva cuantitativa positivista, bajo un diseño experimental, se abordan las carencias identificadas en el léxico de los 30 estudiantes de segundo año de bachillerato paralelo A del colegio de bachillerato Carmen Mora de Encalada. Se considero el uso de métodos teóricos para fundamentar el objeto de estudio, también se utilizó métodos empíricos para obtener resultados detallados sobre el nivel académico de los estudiantes. Luego se aplicó un post-test como instrumento de evaluación, confirmando que el uso de flash cards como recurso didáctico, contribuye de manera positiva al desarrollo léxico y al aprendizaje del idioma inglés. Este impacto positivo se atribuye a la estrategia de memorización y repetición, facilitada por un sistema de actividades interactivas y creativas integradas en el entorno educativo.
Keywords: RECURSO DIDACTICO; SISTEMA DE ACTIVIDADES; FLASH CARDS; VOCABULARIO